The receptor tyrosine kinase Axl in cancer: Biological functions and therapeutic implications. Issue 5 (4th June 2013) - Paccez, Juliano D.; Vogelsang, Matjaz; Parker, M. Iqbal; Zerbini, Luiz F.
<x xml:space="preserve">Abstract</x> The receptor tyrosine kinase Axl has been implicated in the malignancy of different types of cancer. Emerging evidence of Axl upregulation in numerous cancers, as well as reports demonstrating that its inhibition blocks tumor formation in animal models, highlight the importance of Axl as a new potential therapeutic target. Furthermore, recent data demonstrate that Axl plays a pivotal role in resistance to chemotherapeutic regimens. In this review we discuss the functions of Axl and its regulation and role in cancer development, resistance to therapy, and its importance as a potential drug target, focusing on acute myeloid leukemia, breast, prostate and non‐small cell lung cancers.